Evaluation Program of Female's Volleyball Achivement on Junior High School of Bantarkawung sub-district (Journal of Physical Education and Sports, 2018)
Background the researcher wanted to know comprehensively and studied the related phenomena in fostering the achievement of volleyball of junior high school of Bantarkawung, because for 8 years represented Pekalongan Residency but never win at Provincial level in POPDA event. Qualitative approach used is the Countenance Evaluation Model (Stake) in terms of stages: (1) antecedent, (2) process, and (3) outcomes. The instrument used observation guideline, interview guide and check the document. Data analysis used non-statistic qualitative analysis method. This study concluded that: (1) Antecedent was in less category because there was no vision and mission, no tiered training programs, facilities, and infrastructure were not standardized, there was support from government and society, financing gained from government, schools and donors (2) Transaction was concluded as moderate category because the implementation of the training was based on the program, there was no selection of management and coach, no athlete admission mechanism, good coach performance, maximize the use of facilities and infrastructure, adequate transportation, management, coach and athletes received small amount of bonus and incentives, good coordination among the elements, and (3) Outcomes, the training program that had not been good since the expected target was not achieved. The result of this research is benefits to be used as an improvement material and for optimizing the success of Female Volleyball Achievement of Junior High School in Bantarkawung